The Role of Financial Literacy on Student Investment Choices - Sherly Wahyunita Sari; Dini Putri Pebrianti; Agung Threy Wahyu; Herlina Yustati (Yayasan Darussalam Bengkulu, 2023)
The purpose of this study was to determine and measure the impact of the level of financial literacy on the investment choices of students. This study is qualitative descriptive or describes the results of interviews into valid data, data collected based on the results of observation, questionnaires, and direct interviews with students of the faculty of economics and islamic business, uin fatmawati sokarno bengkulu. The results of this study indicate that financial literacy has a significant impact on student investment decisions. The higher the financial literacy possessed by students, the better the investment decisions that will be taken by students.